D'Hier a Demain : Un Aspect de l'Art Actuel : 1968 - 1978 - 1988. (Nice : Direction des Musées de Nice, 1978)
Buraglio, Pierre ; Cane, Louis ; Dezeuze, Daniel ; Dolla, Noël ; Grand, Toni ; Mosset, Olivier ; Pages, Bernard ; Saytour, Patrick ; Viallat, Claude ; Chaumard, Jacques ; Lanneau, Patrick ; Mercier, Elisabeth ; Seree, Gérard
D'Hier a Demain : Un Aspect de l'Art Actuel, Galerie de la Marine, Nice, été 1978
boek